2010
DOI: 10.1111/j.1365-2788.2010.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parenting stress among Malaysian mothers of children with Down syndrome

Abstract: Mean parenting stress among mothers of children with DS significantly differed by behavioural problems in their children. Parenting stress is also significantly correlated with frequent use of acceptance, religious and optimist coping styles, and presence of maternal depressive, anxiety and stress symptoms. However, hierarchical regression analysis identified maternal depression and lack of acceptance of having a child with DS as the most significant predictors of parenting stress in these mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
67
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 33 publications
(79 reference statements)
13
67
3
2
Order By: Relevance
“…Our results confirmed for the most part the mediating role of resilience and social support found in previous studies (Alriksson-Schmidt, Wallander, & Biasini, 2007;Bromley et al, 2004;Heiman, 2002;Holland & Holahan, 2003;Norizan & Shamsuddin, 2010;Pakenham et al, 2005;Rolland & Walsh, 2006;Tak & McCubbin, 2002;Weiss, 2002) Although quality of social support is generally considered the stronger predictor of personal wellbeing (Haber et al, 2007;Kessler & McLeod, 1985), we find no mediating and few direct effects of the quality of social support on the two dimensions of QoL. This could, however, be a methodological artifact as quality of social support was only measured through a single item, potentially revealing less differential effect than other constructs.…”
Section: Adolescentssupporting
confidence: 81%
See 3 more Smart Citations
“…Our results confirmed for the most part the mediating role of resilience and social support found in previous studies (Alriksson-Schmidt, Wallander, & Biasini, 2007;Bromley et al, 2004;Heiman, 2002;Holland & Holahan, 2003;Norizan & Shamsuddin, 2010;Pakenham et al, 2005;Rolland & Walsh, 2006;Tak & McCubbin, 2002;Weiss, 2002) Although quality of social support is generally considered the stronger predictor of personal wellbeing (Haber et al, 2007;Kessler & McLeod, 1985), we find no mediating and few direct effects of the quality of social support on the two dimensions of QoL. This could, however, be a methodological artifact as quality of social support was only measured through a single item, potentially revealing less differential effect than other constructs.…”
Section: Adolescentssupporting
confidence: 81%
“…Our results confirmed for the most part the mediating role of resilience and social support found in previous studies (Alriksson-Schmidt, Wallander, & Biasini, 2007;Bromley et al, 2004;Heiman, 2002;Holland & Holahan, 2003;Norizan & Shamsuddin, 2010;Pakenham et al, 2005;Rolland & Walsh, 2006;Tak & McCubbin, 2002;Weiss, 2002) …”
Section: Adolescentssupporting
confidence: 81%
See 2 more Smart Citations
“…According to this, the difficult experiences of the parents start with the diagnosis of the child and theoretically end with acceptance (Witcher, 1987). In contrast, other studies have shown that parents experience many long-term problems such as burnout (Duran & Barlas, 2014), depression (Harrison & Stuifbergen, 2002), anxiety (Coşkun & Akkaş, 2009), hopelessness (Çatalbaş, Manav, & Ocakçı, 2015) and stress (Hung, Wu, & Yeh, 2004;Norizan & Shamsuddin, 2010) both at the stage of diagnosis and long after diagnosis. In this context, some authors have suggested that very few parents reach the stage of acceptance and the process of adapting to a child with disability continues throughout life (Akdoğan, 2016;Veisson, 1999).…”
Section: Introductionmentioning
confidence: 81%